Improving resource productivity at a crop sequence level - Caviglia, Octavio (2019)
The challenge to increase agricultural production with a minimum environmental impact requires to reach the maximum efficiency in the capture and use of resources such as photosynthetically active radiation (PAR), water, and nitrogen (N). Such requisites are encompassed in the ecological intensification (EI) concept. The aims of this work were to evaluate at a crop sequence level: i) crops yields, ii) water and radiation productivity and its components, i.e. resource capture and resource use efficiency, and iii) partial factor productivity of applied N (PFPN), partial nutrient balance for N (PNB), N uptake and N utilization efficiency of a two-year, three-crop sequence (wheat [Triticum aestivum L.]/soybean [Glycine max (L.) Merr.] double crop – maize [Zea mays L.]) carried-out under EI principles in comparison with the same crop sequence under current farmer practices (FP) in two contrasting locations of the Argentinean Pampas, i.e. Paraná (-31°50′; -60°31′) at the northern Pampas and Balcarce (-37°45′, -58°18′) at the southern Pampas. Experiments were carried-out during four consecutive years, covering two complete cycles of the crop sequence. For the accumulated grain production of the crop sequence, EI management outyielded FP from 13 to 42%, depending on environmental conditions. Maize yield accounted for most of the variation (41–64%) of the accumulated grain yield of crop sequence, whether in EI as in FP. Average grain yield differences between EI and FP treatments were 274 g m−2 for maize, 69 g m−2 for wheat and -2 g m−2 for soybean. Water and radiation productivities of the sequence were higher in EI than in FP (26% for water and 17% for radiation; P < 0.0001), mainly because of increases in resource use efficiencies. EI reduced partial factor productivity of applied N, but improved partial nutrient balance for N as compared with FP. These reductions in partial factor productivity of applied N were less than proportional than the increases in N rate. Moreover, in spite of the higher N rate in EI respect to FP, N utilization efficiency (NutE), i.e. grain per unit N uptake, was higher across all situations in EI. Our results showed that the challenge to obtain high grain yields by increasing N rate in a medium-input system could be achieved even with an increase in NutE. Grain yields improvements, and increases in radiation and water productivity were reached by applying a set of agronomic practices that included improved genetics, crop and fertilizer N management englobed under EI concept.